DISTRIBUSI GURU PENDIDIKAN AGAMA (ANALISIS KEBUTUHAN GURU PENDIDIKAN AGAMA DI SEKOLAH) - Suprapto Suprapto (Badan Litbang dan Diklat Kementerian Agama RI, 2007)
Law Number 20/2003 regarding National Education System illustrates that every student in every educational unit is entitled to accept religious education according to the belief/faith they follow that will be given by those teachers with the same belief/ faith. Therefore, religious education is one compulsory component of so many curriculum components taught to the students in order to achieve the objective of national education. Hence, any of religious educational institutions, both state and private, are obliged to make available religion teachers as per the religion followed by the respective students. The results of 2006 research indicates that: a) distribution of religion teachers in SMPs was distributed relatively evenly in both state andptivate junior high schools (SMPs); b) coordination between schools/ founÂdations, and City/Regency Educational Affairs Offices and Religious AffairsÂ Offices, in fulfilling the need of religious education in both state and private SMPs, was not maximal; c) of SMP schools, if there were less than 10 students of any religion existed in any classroom, they would participate in their religious activities outside the school; d) there were still lacks of religious educational teachers both in state and private SMPs; e) insufficient finances to pay honorarium of the teachers; and J) unequal number of appointed teachers compared to real requirement.